2009
DOI: 10.1194/jlr.m000950
|View full text |Cite
|
Sign up to set email alerts
|

Esterase 22 and beta-glucuronidase hydrolyze retinoids in mouse liver

Abstract: This article is available online at http://www.jlr.org retinol is reesterifi ed ( 3-5 ) for the incorporation into chylomicrons and secreted ( 6 ). In the circulation, chylomicrons are depleted from triglycerides by lipoprotein lipase and are thereby transformed to chylomicron remnants ( 7 ). These remnants acquire apolipoprotein E and are then cleared mostly by parenchymal cells of the liver (i.e., hepatocytes) ( 8-10 ). In hepatocytes, REs are hydrolyzed, and unesterifi ed retinol is associated with retinol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Recombinant mouse Ces1e (called Es22) enzyme shows robust retinyl ester hydrolysis activity and modest, albeit significant, activity as a cholesteryl ester hydrolase (Schreiber et al, 2009). It has been noted that several tissues exhibit triglyceride hydrolysis activity that cannot be accounted for by known lipases (e.g., ATGL, HSL, and others), thus supporting the existence of additional neutral lipases (Zechner et al, 2012).…”
Section: Carboxylesterase Mrna Distribution and Regulation In Mice 47mentioning
confidence: 93%
See 1 more Smart Citation
“…Recombinant mouse Ces1e (called Es22) enzyme shows robust retinyl ester hydrolysis activity and modest, albeit significant, activity as a cholesteryl ester hydrolase (Schreiber et al, 2009). It has been noted that several tissues exhibit triglyceride hydrolysis activity that cannot be accounted for by known lipases (e.g., ATGL, HSL, and others), thus supporting the existence of additional neutral lipases (Zechner et al, 2012).…”
Section: Carboxylesterase Mrna Distribution and Regulation In Mice 47mentioning
confidence: 93%
“…Still, certain CES have long been recognized to play important roles in the biotransformation of ester-and amide-containing compounds to affect the detoxification and/or activation of a variety of xenobiotics, narcotics, and pharmacologic agents in liver and intestine Hosokawa, 1998, 2006). In addition, growing evidence suggests that some CES enzymes may contribute to aspects of lipid metabolism through triglyceride, cholesteryl ester, or retinyl ester hydrolysis (Schreiber et al, 2009;Parathath et al, 2011;Quiroga and Lehner, 2011;Ghosh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In later in vitro studies, it was shown that rat liver carboxylesterases, ES-2 and ES-10 can function as neutral bile salt-independent REHs. More recently, ES-22 has been added to the list of hepatic REH that localize to the ER [24]. …”
Section: Hepatic Metabolismmentioning
confidence: 99%
“…Both proteins are homologous to Es 22 (31). Es22 has meanwhile been identified as a retinyl ester hydrolase (32). Triacylglycerol hydrolase (TGH) is a member of the carboxylesterase family which localizes to the lumen of the endoplasmatic reticulum and likely contributes to the hydrolysis of intracellular triacylglycerol in adipose tissue, adipocytes (33) and hepatocytes (34).…”
Section: Figmentioning
confidence: 99%